Effect of Ala16Val genetic polymorphism of MnSOD on antioxidant capacity and inflammatory response in open heart surgery - (:unkn) unknown (INT INST ANTICANCER RESEARCH, 2008)
Background: Ischemia-reperfusion injury and inflammation in cardiac surgical patients involves complex humoral and cellular interactions. We investigated the effect of genetic polymorphism of manganase superoxide dismutase (MnSOD) a natural antioxidant, on cytokine release and manganesuperoxide dismutase in patients undergoing coronary artery bypass grafting (CABG) with cardiopulmonary bypass (CPB). Patients and Methods: Forty-two patients undergoing elective CABG with CPB were included in the study. MnSOD polymorphism was performed by polymerase chain reaction (PCR). Levels of interleukin-6 and mangane superoxide dismutase (MnSOD) were measured by enzyme linked immunoabsorbent assay (ELISA). Results: Baseline IL-6 did not differ between patients with different MnSOD genotypes. Postoperatively IL-6 levels were significantly higher in all patients but more significantly in V(VV+AV) carriers (p = 0.003). The wild-type AA genotype had the highest preoperative (p<0.05) and postoperative IL-6 level. The MnSOD W genotype was associated with significantly lower preoperative MnSOD levels compared to the AA carriers (p<0.05). Conclusion: These data demonstrate that MnSOD Ala16Val polymorphism influences IL-6 production and baseline MnSOD activity, suggesting that preoperative MnSOD concentration plays a role in cytokine release.
Keywords: polymorphism; MnSOD; superoxide dismutase; open heart surgery; MANGANESE SUPEROXIDE-DISMUTASE; CARDIOPULMONARY BYPASS; CARDIAC-SURGERY; SEQUENCE; ASSOCIATION; DIMORPHISM; RISK